Septic Cavernous Sinus Thrombosis Associated With Bilateral Orbital Cellulitis: A Case Study of A 10 Year Old Rural Girl from Sub-Saharan Region - R. Mohammed-Nafi’u; A. S. Alhassan; E. J. Okon; V. Aliche; J. Asemoh; E. T. Nnadi (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Septic Cavernous Sinus Thrombosis (CST) is a rare infective condition affecting the cavernous sinus in the brain associated with high morbidity and mortality, especially when appropriate and prompt intervention is delayed. Although there is limited data on CST globally, the low prevalence in developing countries may not be unconnected with factors such as poor health seeking behaviour of the people, inadequate healthcare facilities and the dearth of radio-imaging diagnostic techniques, as well as low level suspicion for CST amongst physicians. Here is a case report on a 10 year old indigent nomadic (Fulani) girl diagnosed to have septic cavernous sinus thrombosis and bilateral orbital cellulitis confirmed by enhanced computed tomography (CT) scan of the brain. The case would have been missed, were it not for the intervention of a “Good Samaritan” who facilitated her access to the right medical facility for timely intervention. Objective-To highlight the clinical presentation, management as well as create awareness on the need for a high index of suspicion and early diagnosis of children with CST in order to reduce morbidity and mortality in a resource constraint settings.